Disability of Arm, Shoulder and Hand Using Dash Scoring System after Axillary Dissection for Breast Cancer at Tertiary Care Hospital, Karachi - Prinka; Manal; Rasul, Shahid; Nazeer, Nimra; Effendi, Cemoon (Indus Journal of Bioscience Research, 2025)
Background: Many women experience upper limb dysfunction after axillary dissection for breast cancer. However, the extent and contributing factors remain under examined in local clinical settings. We aimed to assess the level of arm, shoulder, and hand disability using the DASH (Disabilities of the Arm, Shoulder and Hand) score. We will also identify patient and surgical factors associated with increased impairment. Methods: We carried out a cross-sectional study involving 131 women treated with axillary dissection at a tertiary care hospital in Karachi. We recorded demographic data, cancer stage, surgical duration, and employment status. We then categorized DASH scores into mild, moderate, or severe disability and used chi-square tests to explore associations between disability level and clinical variables. Results: Most patients reported moderate (38.9%) or severe (37.4%) disability. Those who underwent shorter surgeries (≤ 2 hours) were more likely to report mild disability (p = 0.01), although moderate disability was also common in this group (p = 0.02). Patients with Stage III breast cancer showed significantly higher rates of severe disability (p = 0.03). We found no significant links between disability and age or employment status, though we observed non-significant trends in both. Conclusion: Upper limb disability remains a frequent outcome after axillary surgery, particularly among women with advanced-stage disease. Shorter operative times may help limit long-term impairment. Routine use of tools like the DASH score and early referral to rehabilitation services may improve functional outcomes and support recovery in this high-risk population